2015
DOI: 10.4274/tjh.2013.0173
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Hospitalised Patients with Multiple Myeloma: Main Characteristics and Risk Factors

Abstract: Objective:Multiple myeloma is a common haematological malignancy and immune dysfunction is the hallmark of the disease. It leads to an increased infection risk, which is still a major cause of mortality. The infection spectrum and characteristics have evolved with the introduction of novel agents. An understanding of risk factors that increase susceptibility to infections is critical in fighting them. This retrospective investigation aimed to establish the incidence and main characteristics of infections in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 54 publications
2
25
1
3
Order By: Relevance
“…Candida albicans was the main pathogenic fungus, consistent with past reports [ 34 ]; however, the infection rate by fungi (5.0%) was lower than a reported rate in patients receiving antitumour therapy (12.3%). Here, viruses were the most common pathogens, mainly including EBV and HBV, in contrast to published research [ 13 , 33 , 35 , 36 ], which found that gram-negative bacteria were the leading pathogens and herpes zoster virus was the main pathogenic virus. Based on data on antitumour therapy in previous studies, chemotherapy can increase the risk of bacterial infection [ 13 ], and bortezomib can increase the risk of herpes zoster virus infection [ 16 , 17 , 37 ]; therefore, the difference in infection spectrum may be related to the therapeutic factors.…”
Section: Discussioncontrasting
confidence: 64%
“…Candida albicans was the main pathogenic fungus, consistent with past reports [ 34 ]; however, the infection rate by fungi (5.0%) was lower than a reported rate in patients receiving antitumour therapy (12.3%). Here, viruses were the most common pathogens, mainly including EBV and HBV, in contrast to published research [ 13 , 33 , 35 , 36 ], which found that gram-negative bacteria were the leading pathogens and herpes zoster virus was the main pathogenic virus. Based on data on antitumour therapy in previous studies, chemotherapy can increase the risk of bacterial infection [ 13 ], and bortezomib can increase the risk of herpes zoster virus infection [ 16 , 17 , 37 ]; therefore, the difference in infection spectrum may be related to the therapeutic factors.…”
Section: Discussioncontrasting
confidence: 64%
“…Neutropenia is a relatively common side effect with many drugs used for MM treatment and increases the risk of infectious complications, especially if severe and prolonged (Palumbo et al , ; Dimopoulos et al , 2015a; Valkovic et al , ). The incidence of neutropenia was similar with IRd and placebo‐Rd (33% vs. 31%; including 18% vs. 18% grade 3, 5% vs. 6% grade 4), and was transient and cyclical in nature.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, respiratory disease was a common cause of death in Puerto Rico, but not among the top causes in the SEER population. The respiratory tract is a common site of infection in MM patients . In addition, in Puerto Rico, there is a high incidence of respiratory diseases likely due to environmental factors like fungal spores, which may partially explain the elevated rate of death from respiratory causes in this population specifically.…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory tract is a common site of infection in MM patients. 28 In addition, in Puerto Rico, there is a high incidence of respiratory diseases likely due to environmental factors like fungal spores, 29 which may partially explain the elevated rate of death from respiratory causes in this population specifically. Future studies could investigate the influence of these co-morbid conditions on prognosis and cause of death in MM patients.…”
Section: Discussionmentioning
confidence: 99%